Microfluidic Cell Sorter (μFCS) for On‐chip Capture and Analysis of Single Cells - Jaehoon Chung; Huilin Shao; Thomas Reiner; David Issadore; Ralph Weissleder; Hakho Lee (2012)
A low-cost and rapid microfluidic cell sorter (μFCS) for circulating tumor cell (CTC) detection, culture and analyses is developed. Based on size separation and molecular characterization, μFCS efficiently enriches CTCs from unprocessed whole blood, allows on-chip culture and molecular profiling, and provides cell retrieval for subsequent analyses. The potential clinical application of the technology is demonstrated by capturing and genetically analyzing CTCs in tumor-bearing mice. Detailed facts of importance to specialist readers are published as "Supporting Information". Such documents are peer-reviewed, but not copy-edited or typeset. They are made available as submitted by the authors. Please note: The publisher is not responsible for the content or functionality of any supporting information supplied by the authors. Any queries (other than missing content) should be directed to the corresponding author for the article.